1994
DOI: 10.1016/s0022-5347(17)35304-1
|View full text |Cite
|
Sign up to set email alerts
|

Serial Prostatic Biopsies in Men with Persistently Elevated Serum Prostate Specific Antigen Values

Abstract: The objective of this study was to determine the need for repeat prostatic biopsies in men whose initial biopsy results revealed no evidence of cancer or atypia. We evaluated 1,136 men who underwent 1 or more prostatic biopsies in a longitudinal prostate specific antigen (PSA) based prostate cancer screening study that called for biopsy if the serum PSA level was greater than 4.0 ng./ml. (Hybritech assay) and findings on rectal examination or ultrasonography were abnormal or suspicious for cancer. Of the 1,136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
210
1
11

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 519 publications
(229 citation statements)
references
References 8 publications
7
210
1
11
Order By: Relevance
“…Previous phases of the Vietnam Veterans Study suggested that exposure to Agent Orange is associated with an increased risk of prostate cancer (Zafar MB et al 2001;Justine L et al 2006;Chamie K et al 2008). A positive family history is also an important risk factor for prostate cancer and, therefore, increases PSA levels (Keetch DW et al 1994). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phases of the Vietnam Veterans Study suggested that exposure to Agent Orange is associated with an increased risk of prostate cancer (Zafar MB et al 2001;Justine L et al 2006;Chamie K et al 2008). A positive family history is also an important risk factor for prostate cancer and, therefore, increases PSA levels (Keetch DW et al 1994). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several epidemiologic studies have reported that low levels of testosterone have an adverse effect on men with newly diagnosed prostate cancer (Messengill JC et al 2003;Schatzl G et al 2003). It is known that prostate cancer can elevate PSA levels (Keetch DW et al 1994). In addition, one study demonstrated that PSA production is associated with steroid hormone receptors (Yu H et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…and to establish a model for the study of late-stage efficacy of potential chemopreventive agents for prostate carcinoma. We chose men with elevated serum PSA but no histological evidence of prostate cancer, as these men are at increased risk for the development of prostate carcinoma (Keetch et al 1994). These men also have a high incidence of high-grade PIN (Brawer.…”
Section: Discussionmentioning
confidence: 99%
“…Routine follow-up of these patients includes biannual PSA and annual repeat biopsy. The risk of finding cancer on repeat biopsy in these men has been estimated to be 15% (in a selected group of men with persistently elevated PSA) (Keetch et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation